Hydrogen activation by [NiFe]-hydrogenases. (9th June 2016) - Carr, Stephen B.; Evans, Rhiannon M.; Brooke, Emily J.; Wehlin, Sara A.M.; Nomerotskaia, Elena; Sargent, Frank; Armstrong, Fraser A.; Phillips, Simon E.V.
Abstract : Hydrogenase-1 (Hyd-1) from Escherichia coli is a membrane-bound enzyme that catalyses the reversible oxidation of molecular H2 . The active site contains one Fe and one Ni atom and several conserved amino acids including an arginine (Arg 509 ), which interacts with two conserved aspartate residues (Asp 118 and Asp 574 ) forming an outer shell canopy over the metals. There is also a highly conserved glutamate (Glu 28 ) positioned on the opposite side of the active site to the canopy. The mechanism of hydrogen activation has been dissected by site-directed mutagenesis to identify the catalytic base responsible for splitting molecular hydrogen and possible proton transfer pathways to/from the active site. Previous reported attempts to mutate residues in the canopy were unsuccessful, leading to an assumption of a purely structural role. Recent discoveries, however, suggest a catalytic requirement, for example replacing the arginine with lysine (R509K) leaves the structure virtually unchanged, but catalytic activity falls by more than 100-fold. Variants containing amino acid substitutions at either or both, aspartates retain significant activity. We now propose a new mechanism: heterolytic H2 cleavage is via a mechanism akin to that of a frustrated Lewis pair (FLP), where H2 is polarized by simultaneous binding to the metal(s) (the acid) and a nitrogen from Arg 509 (the base).